A Clinico-Pathological Study On Mukhadushika And Its Management By Lodhradi Lepa And Arogyavardhani Vati With Special Reference To Acne Vulgaris - Lenka, Bishnupriya; Panda, Pradip Kumar; sahu, Manoranjan (International Research Journal of Ayurveda & Yoga, 2021)
Introduction:-Today’s lifestyle changes like irregular diet, pollution, Stress, hormonal changes are directly affect the skin. It may cause many skin diseases and most common among them is Acne vulgaris which can be correlated with Mukhadushika in Ayurved, which is about 80% of population in the age of of 12-30 years. In Shusruta samhita it is described in Kshudra Rogadhikar. Materials and methods:-A total no. of 30 patients fulfilling the diagnostic criteria of Mukhadushika (Acne vulgaris) were divided into two groups A and B (N=15). Group Ap atient were treated with Lodhradi Lepa (as required) applied externally for 30 days and Group B with Lodhradi lepa (as required) applied externally along with Arogyavardhani Vati 250mg twice daily for 30 days both respectively. Observation and results:-There were 53% and 62.2% of improvement in signs and symptoms in the patients of Group-A and Group-B were observed in this study respectively. The Statistically significant (P<0.05) result was revealed in both Group-A and Group-B but improvement was noticed more in Group-B. Regarding Hormonal (Testosterone and Estrogen) findings, significant(P<0.05) result was noticed in Group B and insignificant result in Group A (P>0.05). Conclusion:-The study revealed that out of 30 cases taken for study, group B showed better result as compared to group A in overall effect. No side effect was noticed during clinical study.